2019
DOI: 10.1051/0004-6361/201834330
|View full text |Cite
|
Sign up to set email alerts
|

Constraining transport of angular momentum in stars

Abstract: Context. Transport of angular momentum has been a challenging topic within the stellar evolution community, even more since the recent asteroseismic surveys. All published studies on rotation using asteroseismic observations show a discrepancy between the observed and calculated rotation rates, indicating there is an undetermined process of angular momentum transport active in these stars. Aims. We aim to constrain the efficiency of this process by investigating rotation rates of 2.5 M stars. Methods. First, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…While Beck et al (2012) found that the cores of low-mass stars at the beginning of the red giant phase rotate 10 times faster than the surface, Deheuvels et al (2015) found that the cores of secondary clump stars rotate between one and three times faster than the envelopes. This is significantly closer to solid-body rotation than the subgiants studied in Deheuvels et al (2014) and consistent with limiting case theoretical arguments that strong coreenvelope coupling must be occurring in secondary clump stars (Tayar & Pinsonneault 2013;Cantiello et al 2014;den Hartogh et al 2019, see also Aerts et al 2019 for a more complete discussion of the available constraints on angular momentum evolution). However, due to the size of previous samples and the methods by which they were selected, it has been difficult to determine whether they accurately represent the full underlying distribution of core rotation rates in the secondary clump.…”
Section: Introductionsupporting
confidence: 82%
“…While Beck et al (2012) found that the cores of low-mass stars at the beginning of the red giant phase rotate 10 times faster than the surface, Deheuvels et al (2015) found that the cores of secondary clump stars rotate between one and three times faster than the envelopes. This is significantly closer to solid-body rotation than the subgiants studied in Deheuvels et al (2014) and consistent with limiting case theoretical arguments that strong coreenvelope coupling must be occurring in secondary clump stars (Tayar & Pinsonneault 2013;Cantiello et al 2014;den Hartogh et al 2019, see also Aerts et al 2019 for a more complete discussion of the available constraints on angular momentum evolution). However, due to the size of previous samples and the methods by which they were selected, it has been difficult to determine whether they accurately represent the full underlying distribution of core rotation rates in the secondary clump.…”
Section: Introductionsupporting
confidence: 82%
“…So far, their impact on the rotation evolution of subgiants and red giants has been addressed only under the debated assumption of the Tayler-Spruit dynamo in radiative interi-ors (Spruit 2002), and its revision based on a different saturation process by Fuller et al (2019). Comparisons with asteroseismic measurements have shown that this process is currently unable to correctly account for the internal rotation of subgiants and red giants (Cantiello et al 2014, den Hartogh et al 2019, Eggenberger et al 2019b, den Hartogh et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…These models that account for rotational and magnetic effects are able to correctly reproduce the internal rotation of the Sun together with the observations of surface velocities of stars in open clusters (Eggenberger et al 2005(Eggenberger et al , 2019a. However, we note that the same models do not provide sufficient coupling to correctly reproduce the asteroseismic core rotation rates of red giants (Cantiello et al 2014;den Hartogh et al 2019), which indicates that an unknown efficient additional AM transport process is needed for subgiant (Eggenberger et al 2019b) and red giant stars (Eggenberger et al 2012(Eggenberger et al , 2017.…”
Section: Orbital Historymentioning
confidence: 72%